Estimation of Stature from Foot Length in Adult Nepalese Population and its Clinical Relevance - Mansur, DI; Haque, MK; Sharma, K; Karki, RK; Khanal, K; Karna, R (Kathmandu University Medical Journal, 2012)
Background Stature is the height of the person in the upright posture. It is an important measure of physical identity. Interrelationships among different body measurements may be used to estimate one from another in case of missing body parts. Objective Stature is an important indicator for identification. There are numerous means to establish stature and their significance lies in the simplicity of measurement, applicability and accuracy in prediction. The current study dealt with developing a regression equation for stature estimation from foot length and to find out the correlation between body height and foot length of Nepalese people. Methods The present study was carried out to establish the regression equation and correlation coefficient between individual’s height and mean foot length. It was conducted on 440 students of age group 17 to 25 years studying in Kathmandu University School of Medical Sciences, Dhulikhel, Nepal. Body height and foot length were measured in centimeter. Results There was significant correlation between height and foot length (r = 0. 703, p < 0.01).The regression equation for height and foot length was found to be Y = 3.179 X + 87.65, where X is the foot length and Y the height. Conclusions This study will help in medico-legal cases in establishing identity of an individual and this would be useful for Anatomists and Anthropologists to calculate stature of adult Nepalese based on foot length. KATHMANDU UNIVERSITY MEDICAL JOURNAL VOL.10 | NO. 1 | ISSUE 37 | JAN - MAR 2012 | 16-19 DOI: http://dx.doi.org/10.3126/kumj.v10i1.6907